A highly stable covalent adaptable network through π-π conjugated confinement effect. (14th June 2022) - Kong, Weibo; Yang, Yunyun; Ning, Jingyi; Fu, Xiaowei; Wang, Yanjun; Yuan, Anqian; Huang, Lei; Cao, Jie; Lei, Jingxin
Abstract: Covalent adaptable networks, which can shuffle chemical bonds through exchange reactions of dynamic covalent bonds in permanent crosslinking networks, could address the pollution issue caused by thermosets. However, the covalent adaptable networks' stability would be deteriorated under external stimulus because of intrinsic dynamic feature of dynamic bonds, which will seriously restrict the stable application of covalent adaptable networks in emerging fields such as self-adaptive materials and devices. In this work, we fabricate a confined dynamic crosslinking polyurethane (CDPU) by constructing π-π conjugation to improve the stability of dynamic disulfide bonds while retaining dynamic activity. The resultant CDPU remains stable even at 160 °C (above its topology freezing transition temperature: 129.2 °C) under single heat stimulus. Whereas this material can be activated under the co-stimulation of 140 °C and 10 MPa stress. Therefore, the CDPU shows improved thermostability and mechanical robustness compared with traditional covalent adaptable networks without confinement effect on dynamic bonds. This strategy provides an effective way to improve the stability of covalent adaptable networks so that they can be applied in emerging fields such as soft robotics, electronic skins, etc. Graphical abstract: Image 1 Highlights: The dynamic thermosetting polyurethane with confinement effect were fabricated. The dynamic thermosetting polyurethane with confinement effect exhibit improved stability. The dynamic bonds with confinement effect can proceed exchange reaction under stimuli of heat and extra force.